Western economic performance in the 1970s: a perspective and assessment - A. MADDISON (PSL Quarterly Review, 2013)
In the “golden age” of the 1950s and 1960s economic growth in the advanced capitalist countries surpassed virtually all historical records. Growth performance in the 1970s then deteriorated significantly, and the pace of inflation more than doubled. The present paper looks at questions related to the slowdown in growth rates and the acceleration of price increases in this period. The author first analyses to what extent favourable performance in the 50s and 60s was due to chance or good policy. Conversely, the extent to which deterioration in the 70s was due to circumstance or bad policy is then considered. Finally, the degree of success or failure of economic policy in the 70s is dealt with.